Formal and Strategic Appropriability Strategies of Multinational Firms: A Cross Country Comparison - Pedro Faria; Wolfgang Sofka (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
International knowledge spillovers, especially through multinational companies (MNCs), have recently been a major topic of discussion among academics and practitioners. Most research in this field focuses on knowledge sharing activities of MNC subsidiaries. Relatively little is known about their capabilities for protecting valuable knowledge from spilling over to host country competitors. We extend this stream of research by investigating MNC appropriability strategies that go beyond formal methods (patents, copyrights, trademarks) to include strategic ones (secrecy, lead time, complex design). We conceptualize the breadth and depth of a firm?s knowledge protection strategies and relate them to the particular situation of MNC subsidiaries. Moreover, we argue that their approaches differ with regard to host country challenges and opportunities. We address these issues empirically, based on a harmonized survey of innovation activities of more than 1,800 firms located in Portugal and Germany. We find that MNCs prefer broader sets of appropriability strategies in host countries with fewer opportunities for knowledge sourcing. However, munificent host country environments require targeted sets of appropriability strategies instead. We deduce that these results are due to a need for reciprocity to benefit fully from promising host country knowledge flows.
Keywords: D83; O32; O31; F23; 330; Appropriability; Multinational Companies; Patenting